2023
DOI: 10.1002/cey2.316
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dispersed ionic liquid electrolytes with high ionic conductivity for ultrastable solid‐state lithium batteries

Abstract: Solid polymer electrolytes (SPEs) have emerged as one of the most promising candidates for building solid‐state lithium batteries due to their excellent flexibility, scalability, and interfacial compatibility with electrodes. However, the low ionic conductivity and poor cyclic stability of SPEs do not meet the requirements for practical applications of lithium batteries. Here, a novel polymer dispersed ionic liquid‐based solid polymer electrolyte (PDIL‐SPE) is fabricated using the in situ polymerization‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…145 Shengyu Qin et al ( 2022) reported a novel polymer dispersed ionic liquid solid polymer electrolyte (PDIL-SPE) fabricated with an in situ polymerization-induced phase separation (PIPS) method. 145 The PDIL was prepared by using a sonication dispersion method to disperse an ionic liquid solution of LiTFSI in [EMIM][TFSI] with a monomer solution of MPEGA and PEGDA in MEA, followed by fabrication of the SPE by sandwiching the PDIL between two glass substrates with 200-μm spacers in between and by polymerization with UV irradiation for the curing process. 145 Apart from good flexibility and interfacial compatibility with Li metal, the PDIL-SPE produced high ionic conductivity of 0.74 mS cm −1 at room temperature, over 1000 h of stable lithium plating/stripping in Li//Li symmetrical cells at 0.5 mA cm −2 current density, and an excellent electrochemical performance evaluation with LiFePO 4 as cathode (157.6 and 98.3 mAh g −1 at 0.1 C and 1 C rates, 90.6% capacity retention after 150 cycles at 1 C).…”
Section: Acs Sustainablementioning
confidence: 99%
See 4 more Smart Citations
“…145 Shengyu Qin et al ( 2022) reported a novel polymer dispersed ionic liquid solid polymer electrolyte (PDIL-SPE) fabricated with an in situ polymerization-induced phase separation (PIPS) method. 145 The PDIL was prepared by using a sonication dispersion method to disperse an ionic liquid solution of LiTFSI in [EMIM][TFSI] with a monomer solution of MPEGA and PEGDA in MEA, followed by fabrication of the SPE by sandwiching the PDIL between two glass substrates with 200-μm spacers in between and by polymerization with UV irradiation for the curing process. 145 Apart from good flexibility and interfacial compatibility with Li metal, the PDIL-SPE produced high ionic conductivity of 0.74 mS cm −1 at room temperature, over 1000 h of stable lithium plating/stripping in Li//Li symmetrical cells at 0.5 mA cm −2 current density, and an excellent electrochemical performance evaluation with LiFePO 4 as cathode (157.6 and 98.3 mAh g −1 at 0.1 C and 1 C rates, 90.6% capacity retention after 150 cycles at 1 C).…”
Section: Acs Sustainablementioning
confidence: 99%
“…145 The PDIL was prepared by using a sonication dispersion method to disperse an ionic liquid solution of LiTFSI in [EMIM][TFSI] with a monomer solution of MPEGA and PEGDA in MEA, followed by fabrication of the SPE by sandwiching the PDIL between two glass substrates with 200-μm spacers in between and by polymerization with UV irradiation for the curing process. 145 Apart from good flexibility and interfacial compatibility with Li metal, the PDIL-SPE produced high ionic conductivity of 0.74 mS cm −1 at room temperature, over 1000 h of stable lithium plating/stripping in Li//Li symmetrical cells at 0.5 mA cm −2 current density, and an excellent electrochemical performance evaluation with LiFePO 4 as cathode (157.6 and 98.3 mAh g −1 at 0.1 C and 1 C rates, 90.6% capacity retention after 150 cycles at 1 C). 145 This was contributed to the novel 3D cocontinuous tubular polymer network structure with abundant −O−CH 2 −CH 2 −O− and continuous ionic liquid phase, both serving as a conductive route for fast Li + transport.…”
Section: Acs Sustainablementioning
confidence: 99%
See 3 more Smart Citations